2013
DOI: 10.3109/10641955.2013.837174
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between circulating levels of adipokines and anti-angiogenic factors in women with BMI <30 and a late-onset preeclampsia

Abstract: Preeclampsia (PE) is a pregnancy-specific disease, directly related to high rates of maternal-fetal morbidity and mortality worldwide. Upregulation of anti-angiogenic factors (soluble fms-like tyrosine kinase-1; sFLT-1 and soluble endoglin; sENG) have been suggested to trigger the maternal endothelial dysfunction observed in PE. Studies focusing on the role of adiponectin and leptin, in normal pregnancy as well as in complicated pregnancies, have revelated interesting findings due to the vascular actions of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…The opposite conclusions have been presented by Eleuterio et al They studied patients with PE, GH, and healthy ones, and they have found no differences in leptin concentrations between groups. The groups were similar in respect of BMI, but only patients with BMI < 30 kg/m 2 were included into the study, what could explain the discrepancies between the aforementioned report and the results of our research where BMI was neither the criterion of inclusion nor exclusion [56]. These differences could also be the result of different gestational ages at the blood sampling.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The opposite conclusions have been presented by Eleuterio et al They studied patients with PE, GH, and healthy ones, and they have found no differences in leptin concentrations between groups. The groups were similar in respect of BMI, but only patients with BMI < 30 kg/m 2 were included into the study, what could explain the discrepancies between the aforementioned report and the results of our research where BMI was neither the criterion of inclusion nor exclusion [56]. These differences could also be the result of different gestational ages at the blood sampling.…”
Section: Discussionmentioning
confidence: 66%
“…The published data on this relationship is inconclusive. Song et al have found that adiponectin levels were unrelated to BMI in PE pregnant women [69], as well as Eleuterio et al who have revealed that adiponectin levels were correlated with BMI only in healthy pregnant women, but not in PE women [56]. According to the results published by Hendler et al, it seems that BMI is crucial: they have revealed that BMI ≥ 25 kg/m 2 was connected with the decrease in adiponectin levels, whereas the increase in concentrations of this adipokine characterized patients with PE of normal weight [58].…”
Section: Discussionmentioning
confidence: 99%
“…The large majority of studies on serum leptin concentrations in women with clinical PE have found upregulated levels in the late second and third trimester [ 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. Compared to pregnant women with uncomplicated pregnancies, in PE leptin does not peak in week 28–32, but continues to increase markedly, only falling again after delivery [ 37 ].…”
Section: Leptin In Pre-eclampsiamentioning
confidence: 99%
“…Leptin is both associated with angiogenic molecules in PE [ 61 ] and is itself a angiogenic factor that can enhance vascular endothelial growth factor synthesis during pregnancy ( Figure 3 ) [ 96 ]. Maternal serum leptin and endothelin-1 (a highly potent vasoconstrictor that is released in conditions of hypoxia) were found to be increased in women with PE and were correlated positively with the degree of FGR in women with PE [ 97 ].…”
Section: Mechanisms For Dysregulated Leptin In Pre-eclampsia and Effects On Fetal Growthmentioning
confidence: 99%
See 1 more Smart Citation